Geographic distribution and clonal diversity of Streptococcus pneumoniae serotype 1 isolates. - Brueggemann, A; Spratt, BG (2003)
Serotype 1 pneumococci are a major cause of serious disease and have been associated with outbreaks but are rarely carried. The high attack rate and lack of coverage of this serotype by the heptavalent conjugate vaccine prompted the characterization of a geographically diverse collection of 166 serotype 1 isolates from recent cases of invasive disease. The isolates were resolved by multilocus sequence typing into 16 clones, which clustered into three major lineages with very different geographic distributions. Lineage A isolates were exclusively from Europe and North America, lineage B isolates were predominantly from Africa and Israel, and lineage C isolates were mainly from Chile. There was no clear association between the presence of individual clones within a country and the prevalence of serotype 1 disease.